تأثير مواعيد العدوى الأولية بعزلة محلية لفيروس واي البطاطاPVY في إنتاجية بعض أصناف البطاطا وفي نسب انتقاله في الدرنات - إسماعيل, عماد; السيد عمر, عبد المحسن; مبيض, وضاح (Latakia University Journal -Biological Sciences Series, 2018)
أظهرت دراسة تأثير مواعيد العدوى الأولية بعزلة محلية لفيروس البطاطا واي ((PVY في إنتاجية أصناف البطاطا بينيلا وسبونتا وبورين وفي نسب انتقال الفيروس إلى درنات تلك الأصناف النتائج التالية: تفاوت موعد تكشف أعراض الإصابة الظاهرية باختلاف الأصناف المدروسة وباختلاف عمر النبات عند تلقيحه بالفيروس, وكانت أكثر الأصناف حساسية للفيروس الصنف بينيلا ثم الصنف بورين وأخيراً الصنف سبونتا. تأثر متوسط الإنتاج من الدرنات في جميع الأصناف المدروسة وفي المعاملات بفروق معنوية. تأثرت نسب انتقال الفيروس في الدرنات باختلاف الأصناف المدروسة والمعاملات, وكانت أقل نسب الانتقال في درنات الصنف بورين (60% في الإصابة المبكرة و0% في الإصابة المتأخرة) ثم في درنات الصنف سبونتا (100% في الإصابة المبكرة و0% في الإصابة المتأخرة) ثم في درنات الصنف بينيلا (96% في الإصابة المبكرة و15% في الإصابة المتأخرة). The study of the effect of time of primary infection with local isolate of PVY on the yield of potato varieties; Penilla, Spunta, Burien; and on PVY-tuber transmission has shown the following results: The time for the appearance of external symptoms was variable according to the studied varieties and to the plant age on the time of inoculation, and according to the symptoms of appearance. Varieties were ranked in the following order: Penilla, Spunta, Burien. The mean yield of potato tubers has been influenced with significant differences in all treatments and varieties. PVY-tuber transmission rates were influenced in all treatments and varieties, and the lowest PVY-tuber transmission rate was for variety Burien (60% for early infection, nil for late infection), followed by variety Spunta (100% for early infection, nil for late infection), and finally variety Penilla (96% for early infection, 15% for late infection).